Assessing the impact of global warming on productivity in emerging economies of Asia. (24th June 2021) - Alvi, Shahzad; Jamil, Faisal; Ahmed, Ather Maqsood
Over the past decade, a consensus has emerged among scientists that the greenhouse gas (GHG) emissions generated by human activities are responsible for changing the earth's climate, which in turn has increased human vulnerability. It is observed that increasing temperatures cause work stress, fatigue and decrease the cognitive abilities of workers. It also affects machines' performance, thereby decreasing labour and capital productivity. Given the importance of productivity for the long-term economic growth and sustainability of economies, this study investigates the impact of global warming on productivity by using a panel data of selected emerging economies of Asia covering a time span of 27 years ranging between 1990 and 2016. The fixed effects model has been used for empirical estimation. The results indicate that global warming has turned out to be a major source of productivity loss.